Projections for the impact of climate change on water balance in a grassland study site - Herceg, András; Kalicz, Péter; Gribovszki, Zoltán (JOURNAL OF LANDSCAPE ECOLOGY, 2024)
The ongoing climate change in Europe is characterized by statistically significant warming in all seasons. Increasing temperatures also affect the precipitation intensity through the hydrological cycle, so that the assumed changes in the distribution and amount of precipitation and the continuously increasing temperatures may increase the rate of water use by plants, making the adaptability of vegetation to climate change a key issue. In the present paper, the hydrological effects of climate change were investigated under typical environmental conditions of a specific agricultural area in Austria. For this purpose, (1) a simple Thornthwaite-type monthly time-step water balance model was developed and (2) the model was used to project the water balance components for the 21st century for (a) a normal root depth (current condition) and (b) a (hypothetically) increased root depth representing the adaptation potential of vegetation to warming. To achieve the main objectives, the model was calibrated and validated with local reference data. The key parameter of the model is the soil moisture holding capacity (SOILMAX), expressed using root depth. The latter was calibrated using available evapotranspiration and soil physics properties. The calibrated model was used for projections using data from four bias-corrected regional climate models. Model runs with normal root depths resulted in increasing annual averages for evapotranspiration and soil moisture, but decreasing annual averages for soil moisture minimums by the end of the 21st century. However, the monthly values indicated that a decrease in soil moisture during the growing season is projected by the end of the 21st century. The vegetation of the selected agricultural area was shown in the model runs to be able to successfully adapt to increasing drought stress by increasing its root zone to its potential maximum.
Keywords: water balance; soil moisture; evapotranspiration; lysimeter; plant available water; regional climate model